PYRITE-ENCRUSTED MIRRORS AT SNAKETOWN AND THEIR EXTERNAL RELATIONSHIPS TO MESOAMERICA. (May 2014) - Gallaga, Emiliano
Abstract : Due to the repatriation process of 20, 475 objects from the site of Snaketown, Arizona, the Arizona State Museum Snaketown Mortuary Documentation Project (2001) was conducted in 2001. This project provided the opportunity to re-analyze the material—which included more than 50 pyrite encrusted mirrors. These items are considered to be one of the most distinctive material elements of the interaction between the American Southwest/Northwest Mexico and Mesoamerica regions and more study is needed. Poorly studied, pyrite mirrors can give insight on numerous topics, such as trade, ideology, and mortuary behavior. This article provides a summary of pyrite mirror analysis, examines the possible functions that may have been performed by the bearers of mirrors at the Snaketown site, and charts the relevance of a site that is one of a few outside of Mesoamerica where large numbers of these artifacts have been found.